Emerging Landscapes of Tumor Immunity and Metabolism - Wu, Fan; Cheng, Ye; Wu, Liangliang; Zhang, Wenling; Zheng, Wubing; Wang, Qian; Cao, Hongyong; Pan, Xiongxiong; Tang, Weiwei (Frontiers in Oncology, 2020)
The metabolic reprogramming of cancer tissue has higher metabolic activity than surrounding tissues. At the same time, the local infiltration of immunosuppressive cells is also significantly increased, resulting in a significant decrease in tumor immunity. During the progression of cancer cells, immunosuppressive tumor microenvironment is formed around the tumor due to their metabolic reprogramming. In addition, it is the changes in metabolic patterns that make tumor cells resistant to certain drugs, impeding cancer treatment. This article reviews the mechanisms of immune escape caused by metabolic reprogramming, and aims to provide new ideas for clinical tumor immunotherapy combined with metabolic intervention for tumor treatment.